Pengembangan Sistem Manajemen Pemesanan Lapangan Olahraga Berbasis Web - Eksantika, Agustina; Abdillah, Lutfy (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The increasing interest in sports in the community at this time is evidenced by the increasing number of field rental businesses. In fact, there are still many field rentals who still implement manual ordering and booking systems, such as coming directly to the location or by telephone. Manual field ordering is considered ineffective because there is a high probability of human error occurring which makes some ordering processes not work properly such as inaccurate information, and there are two orders at one time. The research objective is to produce a system that is used to place online field orders. The development method used is Waterfall, with Unified Modelling Language (UML) system modelling, Hypertext Pre-processor (PHP) system programming, database using MySQL and system testing using Black Box Testing. Data was collected by observing, interviewing and studying literature. This research produces a web-based field ordering information system that can be used by field managers and tenants according to functionality requirements.